Counting Mass Nouns In Guébie - Sande, Hannah; Dawson, Virginia (My University, 2022)
This paper contributes to the growing body of work on countability properties of nouns across languages by investigating the three-way countability distinction in Guébie, an Eastern Kru language spoken in Southwest Côte d’Ivoire. Guébie distinguishes three core categories of noun, which we call true mass, count, and countable mass nouns, and possesses a singulative suffix which converts countable mass nouns into count nouns. We use a mereological model to capture this three-way distinction, and the effects of the singulative suffix.
Keywords: Guébie; mass nouns; Countability properties